PENERAPAN PAKET MANTAP ASI KEPADA CALON AYAH DALAM UPAYA PENINGKATAN PERAN AYAH ASI - Rahmawati, Lisa; Mahdalena Prihatin Ningsih; Rati Purnama Sari (ASMAT: Jurnal Pengabmas, 2024)
Breastfeeding is not an activity that can occur automatically but is an activity that must be well prepared for its success. The success of exclusive breastfeeding and the success of a mother in breastfeeding requires support from all parties, especially the husband and family. Various efforts have been made to increase the achievement of exclusive breastfeeding, both health promotion and government regulations. However, these efforts still do not provide maximum results in achieving exclusive breastfeeding. One effort that can do to increase the role of breastfeeding fathers using the Mantap ASI package so it is hoped that mothers will have maximum support in providing exclusive breastfeeding. This community service aims to increase the role of breastfeeding fathers in efforts to succeed in exclusive breastfeeding through implementation of the Mantap ASI package in the Nanggalo Community Health Center Working Area, Nanggalo District, Padang City. The methods used were lectures, demonstrations, discussions, and oral evaluations with 80 respondents. This activity resulted in an increase in respondents' knowledge and understanding of exclusive breastfeeding, breastfeeding, and the importance of the role of breastfeeding fathers through oral questions given. Apart from that, there was also an increase in the mother's ability in breastfeeding techniques and the father's ability to do oxytocin massage